The Effect of Behavioral Counseling Implementation with Modeling Techniques in Order to Reduce Students' Aggressive Behavior - I Nengah Budi Saputra; Nyoman Dantes; Ni Ketut Suarni (Bisma The Journal of Counseling, 2022)
Experimental research on the effect of implementing behavioral counseling with modeling techniques in order to reduce student aggressive behavior has been widely carried out, but there has been no further study on the results of these studies to be summarized and reassessed so that they can strengthen the results of the research that has been done. This study aims to analyze and describe the effectiveness of the implementation of behavioral counseling with modeling techniques to reduce students' aggressive behavior. This research is library research with the research method used is meta-analysis. The subjects of this research are eleven articles from journals that have been published nationally. Data collection is done by document recording technique. The results of the article analysis by looking for the effect size based on the t-test value so that the effect size result is 2.148, which means it is included in the large category. Factors that influence student aggressive behavior consist of internal factors, namely behavioral patterns, biological factors and frustration, while external factors include poverty, environmental culture, situational, mass media. The results of this analysis strengthen the results of previous studies which state that the implementation of behavioral counseling with modeling techniques has an influence in reducing student aggressive behavior. Therefore this technique is very suitable to be used in order to reduce the aggressive behavior of students.